2020
DOI: 10.18502/ijm.v11i6.2224
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of non-albicans Candida spp. isolated from raw milk and human blood in Alborz and Tehran provinces

Abstract: Background and Objectives: Recent reports indicate high prevalence of fungal infections due to non-albicans Candida spp. which are present in various environments such as raw milk. The quality of milk for fungal normal flora was investigated in this study. Materials and Methods: A total of 262 milk samples were collected directly from milk collection tanks indesignated dairy farms and cultured in SDA media. By further analysis of grown yeasts, 69 non-albicans Candida strains were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
4
0
0
Order By: Relevance
“…Notably, 13 of the 15 C. krusei isolates (73.4%) were also resistant to FLC and KET, 10 of the 15 C. krusei isolates (66.7%) were resistant to flucytosine, and 3 of the 15 isolates (20%) were resistant to amphotericin B. This finding was consistent with a study by Namvar et al (25), but was different from reports by others (8,9,26). Of interest, the rate of resistance to antifungal agents in these C. krusei isolates was lower than our previous findings (12), which might be attributed to the reduction in the use of antifungal drugs during breeding.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, 13 of the 15 C. krusei isolates (73.4%) were also resistant to FLC and KET, 10 of the 15 C. krusei isolates (66.7%) were resistant to flucytosine, and 3 of the 15 isolates (20%) were resistant to amphotericin B. This finding was consistent with a study by Namvar et al (25), but was different from reports by others (8,9,26). Of interest, the rate of resistance to antifungal agents in these C. krusei isolates was lower than our previous findings (12), which might be attributed to the reduction in the use of antifungal drugs during breeding.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the most identified yeast species were C. krusei and C. parapsilosis complex (17.8 and 14.4%, respectively) followed by C. tropicalis, C. kefyr, C. rugosa, and T. asahii (10, 8.9, 8.9, and 6.7%, respectively). These results resembled that of Du et al (2018) and Namvar et al (2020) who reported that Candida spp. other than C. albicans played a pathogenic role in cow's mycotic mastitis.…”
Section: Discussionsupporting
confidence: 89%
“…C. krusei was the predominant species isolated and C. parapsilosis was the second most frequent Candida in their study. Nearly similar results of C. krusei (18.18; 17.4 and 19.8%) were also reported by Ruz-Peres et al (2010), Erbas et al (2017 and Namvar et al (2020), respectively. Considering C. parapsilosis complex, many studies have described their isolation from milk samples with varied frequencies from 0.57 up to 25.4% and reached to 33.4 % in recent study, depending on the sanitary condition and environmental factors (Zaragoza et al 2011;Sartori et al 2014;ErbaŞ et al 2017;Akdouche et al 2018;Hussein et al 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation